2020
DOI: 10.1016/j.clinthera.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcomes Associated With Inpatient Administration of Beers List Medications Following Total Knee Replacement

Abstract: Purpose: Beers List drugs are potentially harmful in older adults and are grouped by level of risk. Over 9000 total knee arthroplasties (TKAs) are performed each year Veterans Affairs (VA) hospitals, primarily on older adults. Minimal data on the administration of Beers List drugs following arthroplasty currently exists in the literature. Our goal was to quantify the risks of these drugs following TKA. We hypothesized that increasing doses of Beers List drugs would be associated with increased risks for readmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a retrospective cohort study of total knee arthroplasties performed in US Department of Veterans Affairs hospitals, Beers List medication administration at any point during hospitalization was associated with increased 30-day readmissions and emergency room visits. 31 Beyond surgical populations, one small retrospective study found longer ICU and hospital LOS in patients with increased PIM administration in the ICU. 32 In our study, we observed that regardless of frailty or cognitive status, perioperative PIM administration was associated with a nearly 2-day increased LOS.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study of total knee arthroplasties performed in US Department of Veterans Affairs hospitals, Beers List medication administration at any point during hospitalization was associated with increased 30-day readmissions and emergency room visits. 31 Beyond surgical populations, one small retrospective study found longer ICU and hospital LOS in patients with increased PIM administration in the ICU. 32 In our study, we observed that regardless of frailty or cognitive status, perioperative PIM administration was associated with a nearly 2-day increased LOS.…”
Section: Discussionmentioning
confidence: 99%
“…While a single dose of these medications perioperatively may not increase risk of postoperative delirium, 30 continued use during hospitalization is associated with adverse postoperative complications, such as hospital readmission. 31 Results suggest that awareness of the harms of such medications has been growing. Indeed, national quality improvement initiatives have been launched with the aim of reducing the use of Beers Criteria medications, 26 and implementation trials have demonstrated reduced administration with a dedicated qualitive initiative program.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients also take various combinations of drugs (mainly anticholinergics or sedative-hypnotics) increasing the risk of pharmacological interactions with other drugs administered during the hospital admission such as sedative, analgesic, etc. Moreover, these multiple associations often induce unwanted symptoms such as fatigue, anxiety, and delirium, increasing perioperative mortality [34]. It is recommended to consider appropriate perioperative drug adjustments by systematically performing the BEERS Criteria for the evaluation of multiple preoperative therapy [35].…”
Section: The Geriatric Patientmentioning
confidence: 99%